The feasibility of stock enhancement as a management tool for dusky kob (Argyrosomus japonicus) in South Africa - Palmer, Ryan Michael (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2008)
The dusky kob, Argyrosomus japonicus, is a popular South African "line fish" whose stocks have dwindled to dangerously low levels of between 1% and 4.5% of pristine spawner biomass per recruit. A. japonicus stocks are currently managed by means of minimum size restrictions and daily bag limits, and as a result of the inability of these measures to facilitate the recovery of the species over a realistic time frame, the need for an alternative management plan has become apparent. Given the status of the stock and management regime, stock enhancement appears to be an appropriate option to be investigated. This study evaluates the feasibility of stock enhancement as a possible management tool to assist with the recovery of this important South African linefish species. By evaluating the genetic and ecological implications related to stock enhancement, identifying a suitable tagging method for post-release monitoring, and evaluating the economic feasibility of such a programme, any fatal flaws would become immediately apparent. This coupled with the required framework for the development of a management plan for stock enhancement of A. japonicus provides direction further research and actions required in order to utilise stock enhancement as a management tool. Due to the nature of stock enhancement, there are several ecological and genetic issues that arise from such a programme. These issues were reviewed and the issues that were relevant to stock enhancement of A. japonicus identified. Ecological concerns that arose included those of competition, disease and seed quality, while genetic issues were concerned mainly in the possible loss of genetic variability and consequent reduction in fitness of the stock. Fortunately the technology exists to evaluate the effects and likelihood of these problems occurring as well as to minimise the likelihood of them occurring. By taking a scientific approach to stock enhancement, hatchery management, and release strategies can be manipulated in such a way as to minimise any negative effects that may be caused. Both ecological and genetic effects of stocking indicate a need for post-release monitoring of stock enhancement programmes. Stock enhancement requires a post-release monitoring programme, which in turn relies on an ability to distinguish between hatchery reared and wild fish. A study was conducted to evaluate the suitability of coded wire tags (CWT), visual implant fluorescent elastomers (VIFE), and oxytetracycline (OTC) as a means of distinguishing between hatchery reared and wild A. japonicus, for the purpose of a post-release monitoring programme. OTC appeared to be the most suitable as it produced 100% retention over a five month period compared to 62% and 61% for VIFE and CWT respectively. OTC is therefore suggested as a tagging method for the purpose of post-release monitoring of the stock enhancement of A. japonicus. To evaluate a possible funding option for stock enhancement of A. japonicus in South Africa, a willingness-to-pay survey, based on a "user pays" approach using recreational fishing permits as a vehicle for payment, included 102 recreational anglers in the Plettenberg Bay area. The survey showed that generally anglers were willing to pay more than the current amount for the recreational fishing permit. This promising result, coupled with the fact that there are approximately 450 000 recreational anglers leads to the belief that there is potential for a substantial increase in the funds generated for the Marine Living Resources Fund through recreational anglers. Stock enhancement should not be ruled out on the basis of economic feasibility yet as there is potential for it to be sustained by the users of the resource. An A. japonicus juvenile production costing model was created taking into account setup and running costs of a hatchery for A. japonicus, based on known parameters from existing facilities, and adjusting them to meet the requirements of a stock enhancement facility. Estimates varied according to the number and size of fish for release (values which can only be decided upon after further research), with setup estimated to be between R 10 000 000 and R 30 000 000 and annual running costs between R 2 400 000 and R 6 700 000 annually. These figures were dependant on the size and number of fish being produced, with production ranging between 100 000 and 5 000 000 fish of between 50 mm and 150 mm, and a broodstock of 150 individuals. Given the need for alternative management of A. japonicus in South Africa and the lack of evidence to suggest that it is an unfeasible option, this project has found no reason why further investigation into the use of stock enhancement for the management of A. japonicus should not proceed further provided the fishery is shown to be recruit limited. The technology and ability to overcome possible ecological and genetic problems exists, a suitable means of tagging for post-release monitoring exists, as does a realistic funding option. There is a substantial amount of research that must be done prior to stocking, for which a base framework is provided.
Keywords: Argyrosomus -- South Africa; Argyrosomus -- Genetics; Fishery management -- South Africa; Fish stocking -- South Africa; Fisheries -- South Africa; Marine ecology -- South Africa; Fish culture -- South Africa